2016
DOI: 10.1242/bio.019497
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol exposure leads to unrecoverable cardiovascular defects along with edema and motor function changes in developing zebrafish larvae

Abstract: Maternal alcohol consumption during pregnancy can cause a series of developmental disorders in the fetus called FAS (fetal alcohol syndrome). In the present study we exposed zebrafish embryos to 1% and 2% alcohol and observed the morphology of heart and blood vessels during and after exposure to investigate motor function alterations, and damage and recovery to the cardiovascular system. The results showed that alcohol exposure could induce heart deformation, slower heart rate, and incomplete blood vessels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
1
14
1
1
Order By: Relevance
“…Additionally, the precardiac cells of the second heart field are outside the heart on day 3, and so we may have missed DNA methylation changes outside of the heart tube itself. Another study that assayed 5‐mC in chicken embryos found that 9‐day hearts had a 5‐mC level between 4 and 5% (Li et al, 2016b), which was slightly higher than what we detected in 8‐day quail hearts (approximately 2.1%). The difference may be due to the different stage and species used.…”
Section: Discussioncontrasting
confidence: 85%
“…Additionally, the precardiac cells of the second heart field are outside the heart on day 3, and so we may have missed DNA methylation changes outside of the heart tube itself. Another study that assayed 5‐mC in chicken embryos found that 9‐day hearts had a 5‐mC level between 4 and 5% (Li et al, 2016b), which was slightly higher than what we detected in 8‐day quail hearts (approximately 2.1%). The difference may be due to the different stage and species used.…”
Section: Discussioncontrasting
confidence: 85%
“…The effects of 1,2-propanediol on vascular development in zebrafish have not been examined previously, which limits the discussion on this topic; however, several studies examined the effects of ethanol on angiogenesis. It has been reported that developmental exposure to ethanol (1% or 2%) disrupts vessel formation in Tg(Fli1:eGFP) zebrafish (similar to Flk1:eGFP), but angiogenic markers were not assessed (Li et al, 2016). Prenatal exposure to ethanol has also been shown to disrupt angiogenesis in brain of neonatal mice, evidenced by reduced vascular density and decreased expression of VEGF receptors (Jégou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since cardiovascular physiology is conserved in humans and zebrafish, the effect of many drugs is comparable between both species ( MacRae and Fishman, 2002 ). Zebrafish embryo has been used to assess the impact of cigarette smoke, alcohol, and recreational drugs on the cardiovascular system in order to understand the effects of maternal consumption during pregnancy in the fetal development, showing alterations in heart rate, morphology, development, and function ( Ellis et al, 2014 ; Mersereau et al, 2015 ; Li et al, 2016 ).…”
Section: Adult Zebrafish and Zebrafish Embryos/larvae In Industrymentioning
confidence: 99%